Peran Badan Pengembangan Sumber Daya Manusia Kementerian Desa Dalam Pengembangan Kapasitas (Capacity Building) Sustainable Tourism Di Desa Wisata - Dhiya Fahriyyah Maritza; Ani, Ani; Mawar Mawar; Djoni Gunanto (FKIP, Universitas Palangka Raya, 2025)
The role of the Human Resources Development Agency (BPSDM) of the Ministry of Villages, Disadvantaged Regions, and Transmigration is central to strengthening capacity building for the implementation of sustainable tourism in Indonesian village destinations. Capacity development for local communities has become increasingly important as village tourism grows as a strategic sector capable of supporting environmental conservation, cultural preservation, and inclusive economic development. By examining policy documents, training reports, and empirical literature on village tourism governance, the analysis highlights how BPSDM contributes to enhancing human resource competencies, improving institutional capacity, and fostering community participation in tourism management. Findings indicate that BPSDM’s initiatives encompass technical tourism training, community empowerment, vocational education, and structured mentoring tailored to the characteristics of each village. These efforts help strengthen local institutions such as Pokdarwis and village-owned enterprises, while also encouraging environmentally responsible behavior aligned with sustainable tourism principles. Collaboration with UN Tourism further enhances training quality through access to global standards and international best practices. Overall, BPSDM’s contribution is evident not only in upgrading technical skills but also in shaping a governance ecosystem that supports effective and competitive sustainable tourism development in village settings. The results emphasize the need for continuous, adaptive, and collaborative capacity-building strategies to optimize the potential of village tourism across Indonesia.